Composing with quantum information: Aspects of quantum music in theory and practice - Helweg Kim (Muzikologija, 2018)
Quantum Music is the title of a research project that opened up an opportunity to investigate the relationship between art and science - to be precise, between music and quantum physics. The idea was to create a platform for innovative work with musical composition and musical instruments inspired by the theories of quantum mechanics. The further development was carefully put into the hands of the different members of the project with such different competences as sound design, physics, musical live performance, composition, light design and musicology. In this connection, I fulfilled the role and interest of the composer as well as representing the performing arts (dance and acting). The aim of my participation was to show how collaboration between music and science could result in a development of different functional approaches to compositional strategies in general and give a new perspective for the artistic thinking in music as well as in the performing arts in general. This article is written as a part of an artistic research and the ideas, statements and conclusions presented in it are to be understood as being directly linked to creative work. But indeed, I also hope this text will provide inspiration to approach music in a new way, both for listeners, musicologists, musicians and other performing artists.